Oceanographic Data Analysis of Parappe Beach, Majene Regency, in Breakwater Planning - Yusman; Sujantoko; Apriansyah (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
Determining the location and dimensions of coastal protection structures, especially breakwaters, must take into account oceanographic data so that the structure can function effectively to protect the coast from damage caused by waves and currents. The method employed in this study is a quantitative approach, utilizing secondary data from the Meteorology, Climatology, and Geophysics Agency (BMKG), National Bathymetry data (BATNAS), and primary data collected directly through field observations, including sedimentation and tidal data. Based on the research conducted, the sedimentation rate for point 1 was 402.405 cm3/year. Point 2 was 503.006 cm3/year. Point 3 was 955.713 cm3/year. For tidal data obtained, the Higher High Water Level (HHWL) is 1.78 m, the Mean High Water Level (MHWL) is 1.2053 m, the Mean Sea Level (MSL) is 0.9203 m, the Mean Low Water Level (MLWL) is 0.6353 m, and the Lower Low Water Level LLWL) is 0.20 m. The dominant wind for 10 years blew from the north, with a maximum wind speed of 11 knots and an effective fetch length of 398.21 km. From the wave forecast, the breaking wave height (Hb) is 76.44 meters, the breaking wave depth (db) is 3.822 meters, the maximum wave height is 2 meters, and the period is 7 seconds.